2016
DOI: 10.1002/cne.23975
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory pathway of the hornet Vespa velutina: New insights into the evolution of the hymenopteran antennal lobe

Abstract: In the course of evolution, eusociality has appeared several times independently in Hymenoptera, within different families such as Apidae (bees), Formicidae (ants), and Vespidae (wasps and hornets), among others. The complex social organization of eusocial Hymenoptera relies on sophisticated olfactory communication systems. Whereas the olfactory systems of several bee and ant species have been well characterized, very little information is as yet available in Vespidae, although this family represents a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 116 publications
(262 reference statements)
2
46
0
1
Order By: Relevance
“…These olfactory sensory tracts, termed T A – T I (Couto et al, 2016), innervate nine distinct clusters of glomeruli, with similar innervation pattern in males and females (Figure 3). We investigated the projection pattern of sensory neurons from basiconic sensilla 2, using specific single sensillum staining.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These olfactory sensory tracts, termed T A – T I (Couto et al, 2016), innervate nine distinct clusters of glomeruli, with similar innervation pattern in males and females (Figure 3). We investigated the projection pattern of sensory neurons from basiconic sensilla 2, using specific single sensillum staining.…”
Section: Resultsmentioning
confidence: 99%
“…The antennal lobes are represented as seen from the ventral side (C,D) or the dorsal side (E,F) . The V. velutina antennal lobe contains nine glomerular clusters termed T A – T I (color coded in C–F ) in both females and males (Couto et al, 2016). The T B cluster is formed by a tight group of small glomeruli in the dorso-caudal region of the antennal lobe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, insect chemosensory proteins (CSPs) have been proposed as carriers to transport chemical stimuli through the sensillar lymph and deliver them to the olfactory receptors (Hansson & Stensmyr, ). Recent studies also report that sensory neurons within the basiconic sensilla of V. velutina preferentially respond to hydrocarbons (Couto et al ., , ). This current study showed that two CSP genes were mainly expressed in the antennae, whereas there was low expression in other tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%